Soy Plant-based Formula with Fiber: From Protein Source to Functional Food - Bardosono, Saptawati; Sunardi, Diana (Indonesian Nutrition Association, 2020)
Several factors are fundamental to support child growth and development, including nutrition. Beside Energy, protein is the key of balanced dietary macronutrients intake as the building block of child growth. While several micronutrients, i.e. calcium, iron, zinc and vitamins are needed for both optimal growth and development. Among protein-rich foods for young children, cow’s milk formula has several limitations, i.e. cow’s milk allergy and low fiber content. Although has a low bioavailability for iron absorption, plant-rich protein can be an alternative for young children to be used, i.e. as a soy isolate protein formula. However, to the fact of low fiber content in soy isolate protein formula, it is then need further consideration to have a fiber enrichment. We highlight the fiber content in child formula to the extent of its benefit for gastrointestinal health in relation to gut movement in preventing constipation, or its role as a functional food with its prebiotics capacity. This article aims to review a suitable type of fiber used for the enrichment for a soy isolate protein formula.